Typomorphic features of minerals and the material composition of the titanium ores of the yastrebow deposits of the southeast of Voronezh anteclise (Proceedings of Voronezh State University. Series: Geology, 2019)
The formations of the yastrebov time in the southeast of the Voronezh anteclise are represented by delta, lagoon, coastal-marine, shallow-water, volcanogenic-sedimentary and volcanogenic formations. Prospective areas for titanium ores are confined to tuffs, tuffites and tuffstone. The content of ilmenite in ores reaches 200–400 kg/m3. Ilmenite has a specific chemical composition, characterized by a high content of MgO and TiO2. Chrome-spinellids are a characteristic mineral with a low content of Al2O3 and high TiO2 and MgO. In addition to their own components for the analyzed ilmenite grains characterized by the presence of magnesium species – geikielite, and manganese – pyrophanite. As inclusions in the studied ilmenites observed monazite, Apatite, and talc. In addition to ilmenite chromespinelides are studied, which are also characteristic of mineral with a low content of Al2O3 and high TiO2 and MgO. There is an inverse correlation between Cr2O3 and FeO.
Keywords: Voronezh anteclyse; tuff; tuffite; tuffstone; ilmenite; chrome-spinellids; paleozoic